Spatial distribution patterns in macrobenthos along a latitudinal transect at the deep-sea observatory HAUSGARTEN. (August 2016) - Vedenin, A.; Budaeva, N.; Mokievsky, V.; Pantke, C.; Soltwedel, T.; Gebruk, A.
Abstract: Spatial distribution patterns of benthic organisms are the focus of various faunal marine studies. However, data on horizontal and bathymetric distribution of the deep-sea macrofauna are still scattered and incomplete, and conclusions are usually based on a low number of samples. Spatial distribution of benthic macrofauna was studied based on the material collected during the RV Polarstern expedition ARK-XXVII/2 in July 2012. Eleven stations along the latitudinal transect at the LTER (Long-Term Ecological Research) observatory HAUSGARTEN in the Fram Strait were taken at depths of about 2.3–2.7 km. Macrofauna was obtained using the box corer. A half core (0.125 m 2 ) was taken at each station and four subcores (0.03 m 2 ) were taken from each core and used for the quantitative analysis. The results suggest that a single, highly variable community with the dominance of polychaetes Galathowenia fragilis and Myriochele heeri inhabits the studied area. No latitudinal gradient in the community was revealed. The prevalence of a spatial variability in the community structure at a scale larger than the full sample per station (0.125 m 2 ) was detected. Several abundant taxa (e.g. the polychaetes Prionospio sp. and Galathowenia fragilis ) tend to form patches within a full sample.